Interaction of T cells and glia in the central nervous system - Murphy, Áine (Trinity College (Dublin, Ireland). Department of Physiology, 2009)
The central nervous system (CNS) was thought of as an immune privileged site, however, it is now known that the CNS is neither isolated nor passive in its interaction with the immune system. Diseases such as multiple sclerosis (MS), and the animal model for MS, experimental autoimmune encephalomyelitis (EAE), develop through inappropriate immune responses in the CNS. MS is a chronic inflammatory disease, caused by demyelination of axons mediated by IFN-y-secreting Th1 cells and IL-17-secreting Th17 cells. It is characterised by CNS infiltrates composed of T cells, macrophages and dendritic cells (DC) and associated with the activation of endogenous glia.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin